1968
DOI: 10.1098/rspa.1968.0051
|View full text |Cite
|
Sign up to set email alerts
|

Electrical control of gas flows in combustion processes

Abstract: The theory of the ionic wind is developed for flame ions travelling towards electrodes of various configurations so that entrainment as well as main stream gas velocities can be predicted. It is shown that, by confining entrainment to specified regions, large flow velocities can be induced at the flame itself, where they can be used to modify a variety of combustion processes. Theoretical maximum values of the flow parameters are calculated for several configurations likely to be of practical use and these are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1971
1971
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…A study of premixed and nonpremixed jet flames under various direct current (DC) and alternating current (AC) conditions recently visualized the three-dimensional nature of ionic wind [3]. Note that Weinberg and colleagues knew the nature of ionic wind [1], however, the visual impact of drastically tilted flame toward a cathode [10] somewhat misled researchers to have a false impression that ionic wind blows from an anode to a cathodeunidirectional.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study of premixed and nonpremixed jet flames under various direct current (DC) and alternating current (AC) conditions recently visualized the three-dimensional nature of ionic wind [3]. Note that Weinberg and colleagues knew the nature of ionic wind [1], however, the visual impact of drastically tilted flame toward a cathode [10] somewhat misled researchers to have a false impression that ionic wind blows from an anode to a cathodeunidirectional.…”
Section: Introductionmentioning
confidence: 99%
“…The separation of these charged species imposes electrical charges on the flow volume, ending neutrality in the flame zone such that the electric body force on the flow volume creates a bulk flow motion, i.e., ionic wind, blowing from the flame toward both electrodes [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…It is known flames conduct electricity due to the presence of free electrons and ions in the combustion zone. Several studies (e.g Lawton and Mayo [15]) showed that when an 4 electric field is applied to a flame, the flame is pulled in the direction of positive ion flow towards the negative electrode. This effect is referred to as the ionic wind induced by the presence of an electric field.…”
Section: Electrical Properties Of the Detonationsmentioning
confidence: 99%
“…Six photo diodes were spaced regularly along the tube to monitor the detonation velocity 15 as it traversed the field section. Three PCB 113A24 pressure transducers were mounted flush with the tube wall at the locations indicated in Figure 2-1.…”
Section: Diagnosticsmentioning
confidence: 99%
“…Electrode GeuinuLiy V. Th1is configurationprvdsteheS opportunity of all geometries used for ionic winds, if exis,:ant, to influence the burning process (19,20,26 This geometry served no further use.…”
mentioning
confidence: 99%